Zebrafish as a potential non-traditional model organism in translational bipolar disorder research: Genetic and behavioral insights (2022)
Bipolar disorder (BD) is a severe and debilitating illness that affects 1-2% of the population worldwide. BD is characterized by recurrent and extreme mood swings, including mania/hypomania and depression. Animal experimental models have been used to elucidate the mechanisms underlying BD and different strategies have been proposed to assess BD-like symptoms. The zebrafish (Danio rerio) has been considered a suitable vertebrate system for modeling BD-like responses, due to the genetic tractability, molecular/physiological conservation, and well-characterized behavioral responses. In this review, we discuss how zebrafish-based models can be suc- cessfully used to understand molecular, biochemical, and behavioral alterations paralleling those found in BD. We also outline some advantages and limitations of this aquatic species to examine BD-like phenotypes in translational neurobehavioral research. Overall, we reinforce the use of zebrafish as a promising tool to investigate the neural basis associated with BD-like behaviors, which may foster the discovery of novel pharmaco- logical therapies.